2000
DOI: 10.1128/aac.44.10.2802-2810.2000
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of the Arginine Deiminase ( arc ) Operon in Penicillin-Tolerant Mutants of Streptococcus gordonii

Abstract: Penicillin tolerance is an incompletely understood phenomenon that allows bacteria to resist drug-induced killing. Tolerance was studied with independent Streptococcus gordonii mutants generated by cyclic exposure to 500 times the MIC of penicillin. Parent cultures lost 4 to 5 log 10 CFU/ml of viable counts/24 h. In contrast, each of four independent mutant cultures lost <2 log 10 CFU/ml/24 h. The mutants had unchanged penicillinbinding proteins but contained increased amounts of two proteins with respective m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…A described streptomycin-resistant S. gordonii Challis strain and its penicillin-tolerant mutant Tol1 were used as model organisms (6,22). Streptococci were grown at 37°C without aeration either in brain heart infusion (Difco Laboratories, Detroit, MI) supplemented with 200 mg/liter of streptomycin (in order to respect the experimental conditions previously described for these isolates) (6,22) or on Columbia agar (Becton Dickinson Microbiology Systems, Cockeysville, MD) supplemented with 3% blood. Escherichia coli XL1-Blue cells were grown at 37°C in Luria-Bertani (LB) broth (Difco) or on LB agar (Difco), supplemented with 50 mg/liter of ampicillin (Sigma Chemicals).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A described streptomycin-resistant S. gordonii Challis strain and its penicillin-tolerant mutant Tol1 were used as model organisms (6,22). Streptococci were grown at 37°C without aeration either in brain heart infusion (Difco Laboratories, Detroit, MI) supplemented with 200 mg/liter of streptomycin (in order to respect the experimental conditions previously described for these isolates) (6,22) or on Columbia agar (Becton Dickinson Microbiology Systems, Cockeysville, MD) supplemented with 3% blood. Escherichia coli XL1-Blue cells were grown at 37°C in Luria-Bertani (LB) broth (Difco) or on LB agar (Difco), supplemented with 50 mg/liter of ampicillin (Sigma Chemicals).…”
Section: Methodsmentioning
confidence: 99%
“…This organism was used as a model because it is poorly lysed by penicillin and provides a well-described isogenic pair of kill-susceptible (parent) and kill-resistant (tolerant mutant Tol1) strains (6,22). Studies were performed with two mechanistically unrelated compounds, i.e., penicillin G and the quinolone levofloxacin.…”
mentioning
confidence: 99%
“…Finally, the high-energy compound carbamoylphosphate is degraded into CO 2 and NH 3 with the concomitant production of an ATP by carbamate kinase encoded by arcC (15,16). However, inactivation of the arc locus in drug-tolerant strains of S. gordonii showed that increased tolerance was not a direct consequence of enhanced expression of the ADI pathway (14).…”
mentioning
confidence: 99%
“…Furthermore, suppression of autolysis in Streptococcus pneumoniae and Staphylococcus aureus had no significant effect on killing by penicillin (6, 10-13). These data collectively indicated that a decrease in the autolytic activity could not fully explain tolerance to bactericidal antibiotics for all drug/pathogen combinations.Characterization of tolerant strains of Streptococcus gordonii that were obtained by cyclic exposure to penicillin at 500 times the MIC showed that two proteins belonging to the arc operon were upregulated in these derivatives (14). The arc operon encodes activities for arginine catabolism.…”
mentioning
confidence: 99%
See 1 more Smart Citation